The Role of Family and Teachers in Instilling Islamic Education to Adolescents in the Digital Age - Musliati; Selvia, Ayu (Yayasan Mentari Madani, 2024)
This article discusses the role of families and teachers in instilling Islamic education for adolescents in the digital era. Today's digital era affects almost all aspects of life, namely health, social, religious and educational aspects. The aim is to try to provide understanding to parents and teachers that the importance of their role in instilling religious education to children in the current era of digital technology. This research is a literature review (library research), or qualitative research, by collecting data from qualitative sources from various books, journals, books and other scientific works as a reference source and then analyzed critically. The development of technology in this digital era brings many impacts, both positive and negative impacts. Islamic education emphasizes the values of the Qur'an to be the source of order in the survival of a Muslim. In order to be more well-organized moral, civil, ethical, and also the behavior of a Muslim. Two educations in Islamic education to instill faith and a strong personality to respond to the current digital era to children, namely: First, creed education is education that must be instilled in every human being related to the recognition, trust and belief in Allah the ruler of nature. Second, worship education is an implication or tangible manifestation of the application of creed